Dinâmica de crescimento urbano no eixo de desenvolvimento Goiânia-Brasília - Santos, Eula Regia Sena (2013)
Brazil has presented a rapid demographic growth in urban areas during the last decades; in fact, the urbanization process was so intense in this country (principally in the twentieth cen-tury, since 1950) that many cities rapidly became connected in a metropolitan conurbation of their urban networks, as a part of a not so succeed national development policy. Currently, this phenomenon is not only observed in large urban centers (as São Paulo and Rio de Janei-ro), but also in medium-sized cities (as Goiânia and Brasília). The intensity of this dynamic transformation of the Brazilian landscape tends to result in an unification of highly urbanized areas, as occur along the BR 060 (a federal road that connects Goiânia to Brasília - Federal District), converging in an axis of biotechnology industries and services, with significant eco-nomic importance to the country and adjacent municipalities. In this sense, this research aimed to analyze the dynamic expansion of urban patches in this development axis (i.e., Goi-ânia-Brasília), through a spatial growth vectors modeling and simulation of future scenarios. Among the results, the study shows a clear trend of urban density in the Metropolitan Region of Goiânia and the Federal District in the coming decades (until 2050). It also highlights the needing to monitor this specific axe, especially at the federal and state government level, in-tending to guarantee a sustainable urban growth, which includes an adequate management of the natural resources, as water and soil availability.